2005
DOI: 10.1016/s0002-9440(10)61192-3
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Prion Is Endocytosed by Human Enterocytes via the 37 kDa/67 kDa Laminin Receptor

Abstract: Some forms of transmissible spongiform encephalopathies result from oral infection. We have thus analyzed the early mechanisms that could account for an uptake of infectious prion particles by enterocytes, the major cell population of the intestinal epithelium. Human Caco-2/TC7 enterocytes cultured on microporous filters were incubated with different prion strains and contaminated brain homogenates in the apical compartment. Internalization of infectious particles was analyzed by Western blotting and immunoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 45 publications
3
87
0
1
Order By: Relevance
“…[16][17][18] expressing enterocytes. Enterocytes are the major cell population of the intestinal epithelium and due to their ability to endocytose pathogens, nutrients and macromolecules, 19 it has been proposed that these cells may represent a major entry site for alimentary prions (Fig. 1).…”
Section: Alimentary Prion Infectionsmentioning
confidence: 99%
“…[16][17][18] expressing enterocytes. Enterocytes are the major cell population of the intestinal epithelium and due to their ability to endocytose pathogens, nutrients and macromolecules, 19 it has been proposed that these cells may represent a major entry site for alimentary prions (Fig. 1).…”
Section: Alimentary Prion Infectionsmentioning
confidence: 99%
“…It has been shown that PrP interacts with these proteins in cis-interactions through its N-terminal tail. Importantly, the laminin receptor is also involved in the binding [24] and the endocytosis of the pathological isoform of PrP, protease resistant isoform of PrP (PrPres) [25]. Although, the precise nature of the binding sites remains to be established, none of the previously described PrP partners could account for the binding described here in immune cells.…”
Section: Discussionmentioning
confidence: 91%
“…4) located at the cell surface and is soluble in the cytoplasm and in the nucleus. At the cell surface the protein serves as a receptor for a variety of substrates including: ECM components such as elastin and laminin; viruses including Sindbis 92 Dengue, 93 Venezuelan equine encephalitis and Adeno-associated virus subtypes 2, 3, 8 and 9, 31,32 as well as cellular 73 and infectious prion proteins 72,74,75 (Fig. 5).…”
Section: The 37 Kda/67 Kda Laminin Receptor Precursor/ Laminin Receptormentioning
confidence: 99%
“…PrP c constitutively cycles between the cell membrane and intra-cellular compartments via the endocytic pathway-a process mediated by the 37 kDa/67 kDa Laminin Receptor Precursor, 72 a high affinity receptor for PrP c73 and PrP Sc . 72,[74][75][76] The prion variants share a common amino acid sequence and differ primarily with regards to secondary structure (PrP Sc exhibits greater β sheet proportion than PrP c -consistent with its higher aggregation propensity) and proteinase K digestion (PrP Sc resists degradation while PrP c does not). 71,77 PrP c has a multitude of physiological functions 70 and the majority of these functions are dependent on the interaction of the prion protein with an array (>70)of proteins.…”
mentioning
confidence: 99%